Women in African traditional religions - Kilson, Marion (Journal of Religion in Africa, 1976)
Following a preliminary discussion of methodological issues associated with studying women in African traditional religions, several ideological and structural aspects of the topic are explored, drawing upon information from thirteen African societies at various levels of social differentiation.
free
Keywords: Africa – Religion; Africa.; Ethnology; Women in religion; Women; African